Transformasi Hidup Perempuan Samaria Dalam Yoh 4:1-42 Sebagai Inspirasi Transformasi Sosial Perempuan Manggarai - Undat, Rikardus; Renleeuw, Dwison Andresco; Hardiyanto, Adrianus; Dani, Kandidus; Baka, Yohanes Jaha; Bria, Fridolin Denri; Senda, Siprianus Soleman; Jegalus, Norbertus; Subani, Yohanes (Jayapangus Press, 2025)
The background to this research is the condition of Manggarai women in NTT who still face structural limitations due to patriarchal culture. The customary practice of belis or dowry often perpetuates subordination, treats women as objects of transaction, and confines their roles to the domestic sphere, thereby limiting their participation in the public sphere. On the other hand, the story of the Samaritan woman in John 4:1-42 offers a radically transformative narrative of liberation from multiple layers of discrimination. This study aims to bridge this gap by analysing how the story of the Samaritan woman's transformation can be adopted as an inspiring theological paradigm for the social transformation of Manggarai women. The method used is descriptive qualitative through literature study. The analysis was conducted in two stages; first, a biblical theological hermeneutical analysis of the text of John 4:1-42 to reveal the meaning of transformation and second, a socio-cultural analysis of the position of Manggarai women. The results of the study show that the transformation of the Samaritan woman was twofold. She underwent a personal transformation, or what is known as restoration of dignity, from social and moral alienation, which directly led to a communal transformation, or the courage to become a prophetic witness in the public sphere. This turning point is symbolised by her action of leaving her water jar, which marks a shift from a domestic focus to a public role. This transformation serves as a powerful counter-narrative to patriarchal structures and practices that diminish the value of women. This study concludes that this biblical narrative has significant contextual potential as a theology of gender liberation. The courage of the Samaritan woman who spoke up can ultimately inspire Manggarai women to move from being objects to empowered subjects, and to take on strategic roles in creating a more just and equitable social order.